The Plaque Puzzle How Dentists, Lab Technicians, and Nurses Are Tackling the Oral-Systemic Disease Mysteries - Alsubaie, Nada Nasser; Alsharif, Bashayer Badawi Mustfa; Alanazi, Eman Hassan Mohammad; Alqhtani, Rana Abdulaziz; Almutairi, Jawharah Dahyan Saud; Otif, Ekhlas Mohammad; Alotaibi , Nahlah Meshal; Alsharif, Hana Badawi Mustfa; Almosallam, Nasser Ali; Almutairi, Naif Musaad; Almutairi, Meshari Faraj; Aldawsari, Abdullah Abdulrahman (Journal of Ecohumanism, 2024)
Oral health is not an isolated aspect of well-being but an essential component of overall health. A growing body of evidence highlights the significant impact of oral diseases, particularly periodontal infections, on systemic conditions such as cardiovascular disease, diabetes, respiratory illnesses, and neurodegenerative disorders. The "oral-systemic link" underscores the need for a multidisciplinary approach in identifying, managing, and preventing diseases that originate in the oral cavity but influence the entire body. General dentists, laboratory technicians, nursing technicians, and phlebotomists each play a distinct yet interconnected role in tackling these oral-systemic disease mysteries. Dentists serve as the frontline professionals in diagnosing and treating conditions like periodontitis, which contribute to systemic inflammation. Laboratory technicians analyze microbial profiles, biochemical markers, and inflammatory mediators to provide diagnostic insights. Nursing technicians assist in patient education, treatment adherence, and post-procedural care, ensuring that patients receive proper oral hygiene guidance to reduce systemic risks. Phlebotomists contribute by collecting and processing blood samples that help track inflammatory markers and correlate oral infections with systemic diseases. This review highlights the collaborative effort among these professionals in advancing research, refining diagnostic methods, and improving patient outcomes. By understanding the complexities of oral-systemic interactions, healthcare providers can develop more comprehensive strategies to prevent and manage diseases that affect both the oral cavity and the entire body.